Desenvolvimento de novas aplicações em análise espectroscópica inorgânica - Gomes Neto, José Anchieta [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
This project focuses on the development of spectroscopic methods for inorganic elemental analysis and explores two main research themes: sample preparation and analytical instrumentation. The first theme deals with the evaluation of the performance of the new commercial digester system with conductive heating in closed vessels for the preparation of animal feed samples (e.g. dogs, cats, fish, poultry, rodents, cattle, horses) and lignocellulosic biomass from forestry and agriculture (invasive species, eucalyptus, bamboo, sugar cane, elephant grass, sorghum biomass) and biomass derivatives (biochar, biocompost) for energetic purposes. This digester, named Simplify, was released on the national market in 2023 by the company Vert. This equipment is the result of a research project initially developed at the Institute of Chemistry of Araraquara/Unesp (FAPESP Grant 2012/02891-7) and more recently at the Vert company (Project PIPE-FAPESP Phase II, Grant 2020/00907-0). The second theme involves instrumentation and will focus on new calibration strategies using single standards for spectroscopic techniques for the determination of inorganic elements and the development and application of 3D printed disposable polymer platforms for graphite furnace atomic absorption spectrometry. The methods to be developed will be evaluated and validated using certified reference materials, alternative techniques/methods and/or addition/recovery tests. Key analytical performance parameters (e.g. selectivity, recovery, linearity, precision, accuracy, limits of detection and quantification, working range) will be determined using established statistical tests
New applications development in inorganic spectroscopic analysis
Keywords: Análise espectral; Química analítica qualitativa; Química inorgânica